The Theory of Asset Choice: Simultaneous Holding of Short and Long Positions in the Futures Market - Schrock, Nicholas W. (Journal of Political Economy, 1971)
Following the expected returns-variance of returns hypothesis of investment behavior, the model of speculative activity developed here establishes conditions leading to the holding of a particular future (asset) with a negative expected rate of return. Such action is rational when the holding of the particular future on which the investor expects to suffer a loss sufficiently reduces the risk associated with his overall position in the market. Certain characteristics of the commodity futures market make it likely that these conditions prevail quite frequently for the large speculator. This reconciles rational economic behavior with the tendency for large speculators to undertake straddle operations.